A tale with a Twist: a developmental gene with potential relevance for metabolic dysfunction and inflammation in adipose tissue - Dobrian, Anca D. (Frontiers in Endocrinology, 2012)
The Twist proteins (Twist-1 and -2) are highly conserved developmental proteins with key roles for the transcriptional regulation in mesenchymal cell lineages. They belong to the super-family of bHLH proteins and exhibit bi-functional roles as both activators and repressors of gene transcription. The Twist proteins are expressed at low levels in adult tissues but may become abundantly re-expressed in cells undergoing malignant transformation. This observation prompted extensive research on the roles of Twist proteins in cancer progression and metastasis. Very recent studies indicate a novel role for Twist-1 as a potential regulator of adipose tissue remodeling and inflammation. Several studies suggested that developmental genes are important determinants of obesity, fat distribution and remodeling capacity of different adipose depots. Twist-1 is abundantly and selectively expressed in the adult adipose tissue and its constitutive expression is significantly higher in subcutaneous vs. visceral fat in both mice and humans. Moreover, Twist1 expression is strongly correlated with BMI and insulin resistance in humans. However, the functional roles and transcriptional downstream targets of Twist1 in adipose tissue are largely unexplored. The purpose of this review is to highlight the major findings related to Twist1 expression in different fat depots and cellular components of adipose tissue and to discuss the potential mechanisms suggesting a role for Twist1 in adipose tissue metabolism, inflammation and remodeling.